The dark side of immunotherapy: challenges facing the new hope in cancer treatment - Teixidor, Eduard; Bosch-Barrera, Joaquim (Annals of Translational Medicine, 2019)
Avoiding immune destruction is an intrinsic cancer characteristic (1). A better understanding of the biological bases underlying this hallmark has allowed a treatment revolution. This new therapeutic option is currently leaving its mark on the cancer treatment strategy for thousands of patients worldwide, and an ever-growing number of clinical trials are increasing its potential future indications in the oncologic setting. Despite these exciting clinical results, immunotherapy treatment has also given rise to new clinical concerns for the future. In this manuscript, we will focus on a recent meta-analysis of the toxicity induced by nivolumab in cancer treatment (2), as well as other issues related to new challenges that immunotherapy implies in the field of oncology.